2018
DOI: 10.2196/10735
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Toward Guided Internet-Based Therapies: Web-Based Survey Study

Abstract: BackgroundInternet interventions have been proposed to improve the accessibility and use of evidence-based psychological treatments. However, little is known about attitudes toward such treatments, which can be an important barrier to their use.ObjectiveThis study aimed to (1) determine attitudes toward guided internet interventions, (2) assess its acceptability compared with other internet-based formats, and (3) explore predictors of acceptance.MethodsA convenience-sample Web-based survey (N=646) assessed att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
106
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 83 publications
14
106
2
6
Order By: Relevance
“…Although providing psychotherapy via telephone or internet (teletherapy) is possible ( Whaibeh et al, 2020 ; Wright and Caudill, 2020 ), many state that face-to-face contact is an essential part of the therapy ( Connolly et al, 2020 ). Thus, the required reduction of face-to-face contacts might lead to a reduced number of patients ( Humer et al, 2020 ; Probst et al, 2020 ) as some reservations against teletherapy have been shown in psychotherapists ( Schuster et al, 2018 ) and the general population ( Apolinário-Hagen et al, 2018 ). This situation might reinforce distress and job anxiety in psychotherapists, especially in those not used to provide teletherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although providing psychotherapy via telephone or internet (teletherapy) is possible ( Whaibeh et al, 2020 ; Wright and Caudill, 2020 ), many state that face-to-face contact is an essential part of the therapy ( Connolly et al, 2020 ). Thus, the required reduction of face-to-face contacts might lead to a reduced number of patients ( Humer et al, 2020 ; Probst et al, 2020 ) as some reservations against teletherapy have been shown in psychotherapists ( Schuster et al, 2018 ) and the general population ( Apolinário-Hagen et al, 2018 ). This situation might reinforce distress and job anxiety in psychotherapists, especially in those not used to provide teletherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, e‐therapy may be an attractive option for individuals who are unemployed as it may overcome cost‐related barriers to treatment seeking. Knowledge of, prior experience with, and attitudes toward e‐therapy are also likely to influence a willingness to try an e‐therapy program (Apolinário‐Hagen et al, 2018). Confidence with technology and level of education may also be more relevant in the context of self‐directed e‐therapy than face‐to‐face given their difference in mechanism of treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Diese Ergebnisse sprechen dafür, dass Patienten die Möglichkeit erhalten sollten, zwischen Selbstmanagement Interventionen und Kognitiver Verhaltenstherapie zu wählen. Das ist auch deswegen wichtig, weil eine kürzlich veröffentlichte im Internet durchgeführte Befragung zu dem Ergebnis kam, dass etwa jeder elfte Befragte eine Behandlung über das Internet für vorteilhafter hält als eine Behandlung im persönlichen Kontakt [43].…”
Section: Behandlung Der Ersten Wahl Bei Leicht Bis Mittelgradiger Depunclassified